1989
DOI: 10.1080/02652038909373738
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurringFusariumtoxins in New Zealand maize

Abstract: Twenty samples of maize collected from healthy growing crops and at harvest time and during storage were screened for four Fusarium toxins (deoxynivalenol, diacetoxyscirpenol, T-2 toxin and zearalenone) by gas chromatography-mass spectrometry and thin-layer chromatography. Seventeen samples (85%) contained one or more of these toxins. Zearalenone was present in 15 samples at levels ranging between 0.1 and 16 ppm. Deoxynivalenol, diacetoxyscirpenol and T-2 toxin were found in 11, 6 and 13 samples respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It is well known that the development of fusaria and other pathogenic fungi in cereals in crops is strongly dependent on weather conditions [Snijders, 1990;Miller, 1994;Parry et al, 1995]. An effect of climate and in particular of precipitation on the occurrence of Fusarium toxins in cereals is indicated by data described by a variety of authors [Blaney et al, 1984[Blaney et al, , 1987Hagler et al, 1987;Hussein et al, 1989;Langseth et al, 1995;Lauren et al, 1996]. Therefore, it was expected that the different climatic conditions during the years would be associated with differences in the pre-harvest occurrence of Fusarium toxins also in southwestern Germany.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the development of fusaria and other pathogenic fungi in cereals in crops is strongly dependent on weather conditions [Snijders, 1990;Miller, 1994;Parry et al, 1995]. An effect of climate and in particular of precipitation on the occurrence of Fusarium toxins in cereals is indicated by data described by a variety of authors [Blaney et al, 1984[Blaney et al, , 1987Hagler et al, 1987;Hussein et al, 1989;Langseth et al, 1995;Lauren et al, 1996]. Therefore, it was expected that the different climatic conditions during the years would be associated with differences in the pre-harvest occurrence of Fusarium toxins also in southwestern Germany.…”
Section: Introductionmentioning
confidence: 99%
“…peanuts (WHO 1990). In New Zealand maize T-2 toxin was detected at 0.01±0.2 ppm in 13 of 20 samples (Hussein et al 1989). The randomly selected grain samples (spring and winter wheat, 2-row and 6-row barley) from Nova Scotia were tested in 1989 and 11% of them had detectable levels of T-2 toxin (between 0.16 and 0.31 ppm) (Stratton et al 1993).…”
Section: Resultsmentioning
confidence: 95%
“…Among trichothecene (TCTC) mycotoxins, T-2 toxin (4 ,15-diacetoxy-8 -(3-methylbutyryloxy)-3 -hydroxy-12,13-epoxytrichothec-9-ene ) is a naturally occurring toxic contaminant in a number of agricultural commodities (Bata et al 1984, Rood et al 1988, Hussein et al 1989. T-2 toxin, which is capable of forming in agricultural products before harvest and during storage, is produced by various species of Fusaria which are widespread fungi on a variety of plants and in soil throughout the cold-temperate regions (Gorst-Allman and Steyn 1979, Yoshizawa et al 1980, Gentry and Cooper 1983, Mann et al 1983, KruÈ ger 1989.…”
Section: Introductionmentioning
confidence: 99%
“…be potential producers of a range of toxic metabolites (mycotoxins) (Lauren et al 1992). Several of these mycotoxins have been shown to occur in New Zealand wheat (Agnew et al 1986;Lauren et al 1991), maize (Hussein et al 1989;Lauren et al 1991), and barley (Lauren et al 1991). Lauren et al (1991) found that for barley, samples from the Waikato had the highest levels of the trichothecenes nivalenol and deoxynivalenol of any of the regions surveyed.…”
mentioning
confidence: 99%